2010
DOI: 10.1152/ajpheart.00288.2010
|View full text |Cite
|
Sign up to set email alerts
|

Chronic treatment with vitamin D lowers arterial blood pressure and reduces endothelium-dependent contractions in the aorta of the spontaneously hypertensive rat

Abstract: Vitamin D has cardiovascular protective effects besides regulating calcium homeostasis. To examine the chronic in vivo effect of a physiological dose of 1,25-dihydroxyvitamin D(3) on the occurrence of endothelium-dependent contractions, spontaneously hypertensive rats (SHR) and Wistar-Kyoto rats (WKY) were treated with the vitamin D derivative for 6 wk. The serum 1,25-dihydroxyvitamin D(3) level of both treated WKY and SHR was significantly higher than in untreated rats while the mean arterial blood pressure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
82
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 60 publications
4
82
1
2
Order By: Relevance
“…During DHT treatment, a difference was noted in Ach-relaxation. By blocking the NO pathway, minor contractions were detected, suggesting the local involvement of the prostanoid system (11,36) and muscarinic Ach receptors (37) in addition to the NO pathway. It has been shown that insulin-dependent relaxation of the large vessels (aorta) and gracilis arterioles are predominantly mediated by NO and endothelium-derived hyperpolarizing factor/potassium channels, respectively (38).…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…During DHT treatment, a difference was noted in Ach-relaxation. By blocking the NO pathway, minor contractions were detected, suggesting the local involvement of the prostanoid system (11,36) and muscarinic Ach receptors (37) in addition to the NO pathway. It has been shown that insulin-dependent relaxation of the large vessels (aorta) and gracilis arterioles are predominantly mediated by NO and endothelium-derived hyperpolarizing factor/potassium channels, respectively (38).…”
Section: Figurementioning
confidence: 99%
“…Wong et al's results demonstrate that vitamin D 3 has a direct vascular effect: lowering prostanoid-dependent vasoconstriction in spontaneously hypertensive rats (SHRs) to the level of Wistar-Kyoto rats (11). Therefore, a role for vitamin D 3 deficiency has been suggested in the pathomechanism of hypertension, because vitamin D 3 treatment also decreases endothelial dysfunction in SHRs (11).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Thus, degeneration of elastin in the arterial wall may lead to aneurysmal dilatation and the de- [22,23]. A recent trial has shown its participation in regulating the expression of many proteins with vascular action, such as vascular endothelial growth factor, type 9 metalloproteinase, myosin, elastin, type 1 collagen, and gamma-carboxyglutamic acid, the latter a protein that protects the vessel against parietal calcification, and also in the suppression of pro-inflammatory cytokines, including interleukin-6 and tumour necrosis factor-alpha in vitro and in vivo [22][23][24]. Moreover, VD suppresses degeneration of elastin in the arterial wall [24].…”
Section: Discussionmentioning
confidence: 99%